Derecho a la muerte digna, descanso para el paciente y familia problema para la iglesia y estado (2014)
The right to a dignified death can be defined as the patient lies either in hospital or at home and has an incurable disease in which the advice of doctors with their families decide to evict the whole both social, economic , family, etc. Thus, in Colombia this practice Deenergizing patient has become controversial across from the church, the state in turn represented by Congress, the high courts and the executive, the church has emphasized while opposition in practice, since they argue that it would not only crime but undermines the will of God in the patient to die with patience but not to see what's disconnected suffer. That is why this article undertakes to sink issue and see views views from other people or other entities